1636 : the Saxon uprising - Flint, Eric (Flint, Eric. Assiti Shards universe., 2011)
King Gustavus of Sweden orders General Mike Stearns of West Virginia to go to Saxony and restore order. Gretchen has been arrested there and is likely to be executed. The revolutionary groups which she has been working with are not about to let that happen, and suddenly there's rioting in the streets and Saxony's ruthless General Baner is determined to suppress the uprising.